The acceptance of refugees. A comparative study of six German neighbourhoods - Friedrichs, Jürgen; Leßke, Felix; Schwarzenberg, Vera (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
In almost all German cities since 2011 accommodations for refugees were established in residential areas, often leading to protest among the residents of respective neighbourhoods. Our study examines the attitudes of residents towards refugees and accommodations for them in their housing area. We conducted face-to-face interviews with representative samples of residents in six such neighbourhoods in Hamburg, Cologne, and Mülheim an der Ruhr, Germany, and obtained a total of 1,800 interviews. Based on hypotheses from prejudice theory and the contact hypothesis we study effects of the social status of the neighbourhood, neighbourhood social capital (collective efficacy), and individual characteristics on refugee discrimination. We find attitudes towards refugees and their accommodations to be predominantly positive, although differentiated in several ways. Discrimination is lower in higher social status neighbourhoods and decreases with years of schooling. Further, contact to refugees reduces prejudice and increases tolerance of larger shares of refugees in one’s neighbourhood. In the final section we suggest, which type of neighbourhood is favourable for refugee accommodations.